Non-muslim’s perception towards purchasing halal cosmetics product / Wan Muhamad Hanan Wan Ibrahim - Wan Ibrahim, Wan Muhamad Hanan (2016)
This study is about non-Muslims perception towards purchasing halal cosmetics product. The purpose of this study is to determine the non-Muslims perception towards halal cosmetics product, to describe the non-Muslims intention to purchase halal cosmetics product and to investigate the relationship between non-Muslims perception towards purchasing halal cosmetics product and non-Muslims intention to purchase halal cosmetics product. The data set is collected through self-administered questionnaire and convenient non-probability random sampling method. A sample of 168 questionnaires was collected from non-Muslims respondents conveniently by their attire in Wilayah Persekutuan, Kuala Lumpur. Data obtained were than analyzed using Statistical Package for Social Science (SPSS). The finding revealed that there is a significant relationship between non-Muslims perception towards purchasing halal cosmetics product and non-Muslims intention to purchase halal cosmetics product. The results indicate that the non-Muslims attitude, subjective norm, and perceived behavioural control were found to be positive influence on intention to purchase halal cosmetics product. Other than that, non-Muslims perception towards halal cosmetics product has a very strong and positive relationship between non- Muslims intention to purchase halal cosmetics product. Moreover, this research reveals that non-Muslims perception towards halal cosmetics product affects the non-Muslims intention to purchase halal cosmetics product.